Pseudoangiomatous Stromal Hyperplasia: A Rare Cause of Breast Lump in a Premenopausal Female - Zeeshan Kareem; Sandhya Iyer; Mansha Singh (Journal of Clinical and Diagnostic Research, 2017)
Pseudoangiomatous Stromal Hyperplasia (PASH) of the breast is a rare benign proliferating breast condition. We report a case of a 26- year-old female who was being worked up for infertility and was incidentally noted to have a well defined lump in the left breast. Fine Needle Aspiration Cytology (FNAC) and core needle biopsy of the lump were suggestive of benign breast disease. Patient underwent excision of the lump. Histopathology report of which was suggestive of PASH of the breast.